2017
DOI: 10.1016/j.molp.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

5-Methylcytosine RNA Methylation in Arabidopsis Thaliana

Abstract: 5-Methylcytosine (mC) is a well-characterized DNA modification, and is also predominantly reported in abundant non-coding RNAs in both prokaryotes and eukaryotes. However, the distribution and biological functions of mC in plant mRNAs remain largely unknown. Here, we report transcriptome-wide profiling of RNA mC in Arabidopsis thaliana by applying mC RNA immunoprecipitation followed by a deep-sequencing approach (mC-RIP-seq). LC-MS/MS and dot blot analyses reveal a dynamic pattern of mC mRNA modification in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
254
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(267 citation statements)
references
References 58 publications
13
254
0
Order By: Relevance
“…There is also evidence that tRNA modifications, including m22G, might be specifically involved in the post‐transcriptional regulation of DDR pathways by promoting increased translation of DDR proteins (Begley et al, ). The m5C metabolite, accumulated in NaB‐treated seeds at the radicle protrusion stage, has been recently suggested as a novel epitranscriptome marker of plant development in Arabidopsis (Cui et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that tRNA modifications, including m22G, might be specifically involved in the post‐transcriptional regulation of DDR pathways by promoting increased translation of DDR proteins (Begley et al, ). The m5C metabolite, accumulated in NaB‐treated seeds at the radicle protrusion stage, has been recently suggested as a novel epitranscriptome marker of plant development in Arabidopsis (Cui et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(1) Antibodies specific to a modification are used to immunoprecipitate fragmented mRNA, and RNA sequencing (RNAseq) is applied to input and immunoprecipitated RNA fractions. Significant enrichment then identifies mRNA intervals likely to contain a modified nucleotide (Dominissini et al, 2012;Meyer et al, 2012;Edelheit et al, 2013;Schwartz et al, 2013;Delatte et al, 2016;Dominissini et al, 2016;Li et al, 2016;Cui et al, 2017). (2) Modified nucleotides are specifically derivatized using unique reactivity with an appropriate compound, and the presence of the derived nucleotide is read either as a mutation signature or as a stop upon reverse transcription (Squires et al, 2012;Carlile et al, 2014;Lovejoy et al, 2014;Schwartz et al, 2014a;Li et al, 2015;David et al, 2017;Enroth et al, 2019;Sun et al, 2019;Zhang et al, 2019b).…”
Section: Seeing Mrna Modifications: High-throughput Sequencing Delivementioning
confidence: 99%
“…Transcriptome-wide m 5 C maps at variable depth are by now available for several tissues and cell lines of human/mouse (Squires et al 2012;Hussain et al 2013b;Khoddami and Cairns 2013;Blanco et al 2016;Amort et al 2017;Legrand et al 2017;Yang et al 2017;Wei et al 2018;Chen et al 2019;Huang et al 2019;Sun et al 2019), zebrafish (Yang et al 2019b), plant (Cui et al 2017;David et al 2017;Yang et al 2019a), archaeal (Edelheit et al 2013) and even viral (Courtney et al 2019a;Courtney et al 2019b) origin, persistently identifying sites with biased distribution in mRNAs and/or ncRNAs, reviewed in (Trixl and Lusser 2019). Several studies have further suggested regulatory roles for m 5 C in mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches based on high-throughput RNA-seq as a readout have been developed to map m 5 C. One is to perform an immunoprecipitation of cellular RNA fragments with anti-m 5 C antibodies (m 5 C-RIP) (Edelheit et al 2013;Cui et al 2017). Other approaches use enzyme-trapping, either by over-expressing a mutant MTase that cannot resolve the covalent enzyme-RNA intermediate (methylation iCLIP or miCLIP) (Hussain et al 2013b), or by prior incorporation of 5-azacytidine into cellular RNA, which then covalently traps endogenous MTases to their substrates (Aza-IP) (Khoddami and Cairns 2013).…”
Section: Introductionmentioning
confidence: 99%